Disparities in Accessibility of Certified Primary Stroke Centers - Mullen, Michael T. (Stroke, 2014)
BACKGROUND AND PURPOSE: We examine whether the proportion of the US population with ≤ 60 minute access to PSCs varies based on geographic and demographic factors. METHODS: Population level access to PSCs within 60 minutes was estimated using validated models of prehospital time accounting for critical prehospital time intervals and existing road networks. We examined the association between geographic factors, demographic factors, and access to care. Multivariable models quantified the association between demographics and PSC access for the entire US and then stratified by urbanicity. RESULTS: Of the 309 million people in the US, 65.8% had ≤ 60 minute PSC access by ground ambulance (87% major cities, 59% minor cities, 9% suburbs, and 1% rural). PSC access was lower in stroke belt states (44% vs. 69%). Non-Whites were more likely to have access than Whites (77% vs. 62%) and Hispanics were more likely to have access than non-Hispanics (78% vs. 64%). Demographics were not meaningfully associated with access in major cities or suburbs. In smaller cities there was less access in areas with lower income, less education, more uninsured, more Medicare and/or Medicaid eligibles, lower healthcare utilization and healthcare resources... CONCLUSIONS: There are significant geographic disparities in access to PSCs. Access is limited in non-urban areas. Despite the higher burden of cerebrovascular disease in stroke belt states, access to care is lower in these areas. Select demographic and healthcare factors are strongly associated with access to care in smaller cities, but not in other areas, including major cities.